Peran Art Jakarta dalam Memajukan Seni Kontemporer Indonesia: Perspektif Sejarah Sosial Seni - I Gusti Ayu Putu Pratiwi; Hendra Santosa (Segara Widya : Jurnal Penelitian Seni, 2025)
This research is grounded in the shifting landscape of Indonesian contemporary art following the Reformasi era, during which art institutions began to play a crucial role in mediating values, social networks, and the structure of the cultural field. Art Jakarta, as the largest art fair in Indonesia, exemplifies how an art institution functions not only as an exhibition platform but also as an active cultural agent. This study explores the role of Art Jakarta in shaping artistic value and social structure within Indonesia’s contemporary art world. Using the social history of art approach and Pierre Bourdieu’s theory of the cultural field, the research examines how Art Jakarta operates as a symbolic, economic, and social arena where cultural actors interact, compete, and negotiate positions. The study employs a qualitative methodology, involving in-depth interviews, participatory observation, and document analysis of curatorial texts and art media. Thematic and contextual analysis is used to understand Art Jakarta’s institutional role in influencing the social dynamics of art. Findings reveal that Art Jakarta contributes to symbolic legitimacy, strengthens artists’ social capital, and shapes the narrative of the contemporary art market. While it creates opportunities for professional growth and cross-institutional collaboration, the fair also reproduces structural exclusivity through curatorial selection and gallery representation. This study concludes that Art Jakarta functions not merely as a marketplace but as a strategic cultural institution that actively influences the development, direction, and social history of contemporary Indonesian art.